Answer:
(- 4, 17 ) and (2, - 1 )
Explanation:
Given the 2 equations
y = x² - x - 3 → (1)
y = - 3x + 5 → (2)
Substitute y = x² - x - 3 into (2)
x² - x - 3 = - 3x + 5 ( subtract - 3x + 5 from both sides )
x² + 2x - 8 = 0 ← in standard form
(x + 4)(x - 2) = 0 ← in factored form
Equate each factor to zero and solve for x
x + 4 = 0 ⇒ x = - 4
x - 2 = 0 ⇒ x = 2
Substitute these values into (2) for corresponding values of y
x = - 4 : y = - 3(- 4) + 5 = 12 + 5 = 17 ⇒ (- 4, 17 )
x = 2 : y = - 3(2) + 5 = (- 6 + 5 = - 1 ⇒ (2, - 1 )